Poor implementation of teaching material in the english language teaching-learning process on the students of senior year at Kleber Franco Cruz high school, academic year 2014-2015. - Correa Hidalgo, José Junior (2014)
The topic of the thesis hereby is: Poor implementation of teaching material for the English language teaching-learning process on the students of Senior Year at Kleber Franco Cruz high school, academic year 2014-2015, which is highly relevant because teaching materials are the ideal tool that teachers need to carry out a dynamic and clear lesson for their students. The central problem is the poor implementation of teaching materials in the English language teaching-learning process. This decreases the interest of students to learn the language. The general objective of the thesis is to determine how teaching materials can be applied in the English language teaching-learning process.